The Effect of Prolanis Exercise Activities on Decreasing Blood Sugar Levels in Diabetes Mellitus Patients - Fitri Silvia; Mappeaty Nyorong; Miskah Afriany; Lucia Lastiur (Journal La Medihealtico, 2021)
Diabetes exercises are physical exercises designed according to age and physical status and are part of the treatment of diabetes mellitus. When a person does physical exercise in the muscles of the body, the heart system and blood circulation and breathing are activated. Therefore, the body's metabolism, fluid and electrolyte balance and acid base must adjust. Muscles will use free fatty acids and glucose as a source of energy or energy. When physical exercise begins glucose originating from muscle-muscled glycogen when physical exercise starts being used as a source of energy. Assessing the effect of the implementation of prolanis exercise activities on reducing blood sugar levels in patients with Type 2 Diabetes Mellitus in Puskesmas Padangmatinggi in 2019. This type of research is quantitative with a quasi-experimental design that designs using one group pretest-posttest, when this study was conducted in January-April year 2020. The population in this study were all patients with diabetes mellitus who follow prolanis gymnastics in Padangmatinggipuskesmas with purposive sampling technique, namely the determination of the sample by specifying specific characteristics consisting of 15 intervention / experimental groups and 15 control groups 15 people The results showed that there was an effect of the application of prolanic exercise activities to reduce blood sugar levels in patients with type 2 diabetes at Padangmatingi Public Health Center in Padangsidimpuan with a P-Value of 0.007, and there were differences in blood sugar levels in the intervention and control groups with a P. Value of 0,000.